1975
DOI: 10.1113/jphysiol.1975.sp010888
|View full text |Cite
|
Sign up to set email alerts
|

The effect of substances releasing intracellular calcium ions on sodium‐dependent calcium efflux from guinea‐pig auricles.

Abstract: SUMMARY1. 45Ca efflux and resting tension were measured in isolated guinea-pig auricles under conditions known to change the intracellular free Ca ion concentration.2. In the presence of [Na]o, caffeine (2 mM) increases 45Ca efflux, but does not produce a contracture, while in the absence of [Na]0 and [Ca]o caffeine causes a contracture without increasing 45Ca efflux. Adrenaline (10-5 -10-4 M) with or without theophylline (0.5-1 0 mM) has no effect on either 45Ca efflux or resting tension.3. In the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
2

Year Published

1980
1980
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(64 citation statements)
references
References 39 publications
(54 reference statements)
7
55
2
Order By: Relevance
“…This result is consistent with the finding of Busselen and Van Kerhove (1978) that caffeine increased the efflux of "'Ca from goldfish ventricle in the absence of Na.. However, Jundt et al (1975) noted that in guinea pig atria, caffeine in the absence of extracellular Na produced a contracture, without increasing "Ca efflux . Thus, the relative importance of the Na,,-independent Ca extrusion system in cardiac tissue may vary from preparation to preparation .…”
Section: Discussionsupporting
confidence: 82%
“…This result is consistent with the finding of Busselen and Van Kerhove (1978) that caffeine increased the efflux of "'Ca from goldfish ventricle in the absence of Na.. However, Jundt et al (1975) noted that in guinea pig atria, caffeine in the absence of extracellular Na produced a contracture, without increasing "Ca efflux . Thus, the relative importance of the Na,,-independent Ca extrusion system in cardiac tissue may vary from preparation to preparation .…”
Section: Discussionsupporting
confidence: 82%
“…The late sustained tension seems to be caused by the inflow of Ca from the extracellular sites, because it lasted as long as the muscle was exposed to Ca-rich solution containing caffeine and was dependent on external Ca concentration. JUNDT et al (1975) showed that the Ca turnover rate across the membrane was increased by caffeine in the presence of Na. We have, however, no direct evidence concerning the origin of late tension.…”
mentioning
confidence: 99%
“…This value is not universally accepted (Jundt, Portzig, Reuter & Stucki, 1975), although their appears to be agreement that in squid axons Na-Ca exchange is electrogenic (Blaustein, 1976;Baker & McNaughton, 1976). These experiments do not exclude, for instance, the possibility that the carrier is voltage dependent.…”
Section: Removal Of Acsmentioning
confidence: 99%